Naphthalene Induced Hemolysis With Acute Kidney Injury in a g6pd Deficient Boy - Islam, Md Nazrul; Ahmed, Abu Saleh; Khan, Mohammad Ehasun Uddin; Rahman, Hossain Muhammad Mustafijur; Rahman, GM Hafizur; Anwar, ASM Tanim; Badal, Md Dilder Hossain; Faisal, Amanur Rasul Md; Khan, Mohammad Ashikur Rahman; Moitry, Mahnaz Islam (Journal of Dhaka Medical College, 2023)
Naphthalene is a chemical substance which is widely used as moth repellent, insecticide and deodorizer. Naphthalene mothballs are potent hemolytic agents specially for pediatric group and Glucose 6 phosphate dehydrogenase (G6PD) deficient individuals. Our patient, a 14-year-old boy got admitted in our institution with progressive pallor, jaundice, hematuria and oliguria. He used to chew naphthalene mixed flavored raw rice for the last six months. On investigation he was found to have features of intravascular hemolysis and AKI necessitating hemodialysis with blood transfusion. His G6PD activity was below normal. After seven sessions of Hemodialysis (HD) his renal function recovered and discharged accordingly. One month post discharge follow up was normal. J Dhaka Med Coll. 2021; 29(1): 123-126